2019 22nd International Conference on Electrical Machines and Systems (ICEMS) 2019
DOI: 10.1109/icems.2019.8921839
|View full text |Cite
|
Sign up to set email alerts
|

Torque Optimization of a Seven-Phase Bi-harmonic PMSM in Healthy and Degraded Mode

Abstract: Compared to sinusoidal machines, a bi-harmonic machine (with only two harmonics of similar value in the electromotive force spectrum) can develop torque of comparable values under three kinds of supply: with only first or both first and third sinusoidal currents. Therefore, more degrees of freedom for the control of the machine can be achieved. In this paper, the specificities of a 7-phase bi-harmonic permanent magnet synchronous machine (PMSM) are investigated under different control strategies, such as maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…A commercial five-phase SPM machine is taken as reference [26], and a three-phase V-shaped IPM machine [9] and a seven-phase axial flux machine (AFM) are designed. Based on the previous AFM machine, a third rotor with V-shaped PMs of different poles is designed [27], which is a hybrid flux (radial and axial) machine (HFM). Considering the magnetic flux direction, PM shape and the number of phases, four machines were selected for comparison.…”
Section: Introductionmentioning
confidence: 99%
“…A commercial five-phase SPM machine is taken as reference [26], and a three-phase V-shaped IPM machine [9] and a seven-phase axial flux machine (AFM) are designed. Based on the previous AFM machine, a third rotor with V-shaped PMs of different poles is designed [27], which is a hybrid flux (radial and axial) machine (HFM). Considering the magnetic flux direction, PM shape and the number of phases, four machines were selected for comparison.…”
Section: Introductionmentioning
confidence: 99%
“…Optimizing the dimension of PMs and slot entrance designs, along with an optimal selection of slot/pole combinations for OR-SPMSM, has a high impact on the slotting effect and air-gap flux density of the machine and hence effectively results in the cogging torque reduction. In addition, with the advent of power electronic converters, the multiphase drive system, with advantages such as reduction of torque pulsation and providing higher torque pulsation frequencies, can apply to electric motor drive systems [19][20][21][22][23][24][25][26]. Marmaras et al [3] studied the behavior of the EV drivers and their impact on electricity and transport electrification systems.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that the torque can be increased by 8.6% with negligible torque ripple. Seven-phase dual-harmonic PMSMs are modelled and control systems developed for healthy and faulted operation in [20], [21]. A further interesting research, related to the low-order harmonic utilisation in n-phase machines, was presented in [22], where a novel heuristic algorithm for symmetrical fractional slot concentrated winding multiphase PMSM design, which maximizes the output average torque under the current harmonic injection, was developed.…”
Section: Introductionmentioning
confidence: 99%